Input-output linearization of SISO nonlinear time-varying delay systems. Issue 1 (July 2017) - Haidar, Ihab; Nicolau, Florentina; Barbot, Jean-Pierre; Aggoune, Woihida
Abstract: The present paper deals with the input-output linearization of nonlinear time-varying delay systems with delays in the input and the output. We introduce an extension of the Lie derivative for time-varying delay systems. We derive sufficient conditions for existence of a causal and bounded nonlinear feedback that linearizes the input-output behavior and stabilizes the system.